Targeting Precision Medicine: Evidence from Prenatal Screening - Conner, Peter; Einav, Liran; Finkelstein, Amy; Persson, Petra (Journal of Political Economy, 2025)
We study the introduction of a noninvasive prenatal screening—cell-free DNA (cfDNA) screening—which is used to target a more costly invasive test that elevates miscarriage risk. Using Swedish administrative data, we document that coverage of cfDNA substantially increases cfDNA screening and reduces invasive testing. We develop and estimate a stylized model of prenatal choices and find that narrow targeting of cfDNA coverage can improve outcomes and reduce costs, while broader coverage also improves outcomes but with increased costs. These findings point to the potential gains from well-designed targeting of screening but at the same time highlight the importance of the targeting design.